ANALISIS PENGARUH PROMOSI PERSEPSI HARGA DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA VEGA ZR - Achmadi Aziz, 09.05.51.0086 (Students Journal of Economic and Management, 2013)
This research is grounded by the decreased sale ofÂ Yamaha when compared to its competitors such as Suzuki and Honda. As for the problem in this research is âinfluenceÂ perceptiont of price, perception of quality products, and promotional product purchasing decisions influence the Yamaha motorcycle?â The purpose of this research is to analyze the effect of each variable promotion (X1), perceptiont of price (X2), and decaint (X3) on purchase decision (Y). In this research, data were collected through questionnaire method against 100 respondens purchaser and user of Yamaha motorcycles in Weleri Kendal with the purposive sampling. This method is used to determine the responses of respondents for each variable. The calculation results obtained that the factors having the most positive and significant influenceon purchase decisionsis promotion. Price also has a positive and significant impact on purchasing decisions. The decaint factors has a positive and significant impact onpurchasing decisions. Keywords: promotion, perception of price, decaint , purchasing decisions.